Antifibrinolytic Action of the Anticoagulant Split Product of Fibrinogen - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1968)
The purified anticoagulant split product of fibrinogen has antifibrinolytic and anti-fibrinogenolytic activity. This was investigated by lysis times of fibrin and by the rate of disappearance of fibrinogen in plasma and in a purified system. A new method was used to measure fibrinogenolytic activity. In the experimental system which we have used no indication of additional breakdown of the anticoagulant split product in the presence of fibrinolysin was obtained.